Topology Optimization of a Robot Gripper with nTopology - Beatriz Monteiro; Francisca Rocha; Jose Costa (U.Porto Journal of Engineering)
The robot gripper works analogously to the human hand, being the end effector of a robotic mechanism and acting as a bridge between the robot and the environment. A topology optimized gripper can be fully functional while allowing weight reduction. In this paper, the topology optimization of a 316L-SS four-clamp gripper capable of withstanding a 2 N load was conducted using the nTopology software. Fusion360 static stress analysis showed a reduction of 43% in weight, keeping the safety factor above 3, and leading to a displacement of 0,0067 mm. Finally, the maximum induced stress was shown not to cause permanent deformation of the clamp since it was observed to be inferior to the yield strength of 316L-SS.